2009
DOI: 10.1111/j.1552-6569.2008.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus Bilateral Middle Cerebral Artery Detection of Right‐to‐Left Shunt by Power M‐Mode Transcranial Doppler

Abstract: Unilateral detection of ET by power M-mode transcranial Doppler is equivalent to bilateral detection to assess RLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, TCD is considerably less invasive for the patient, and the Valsalva maneuver, which signifi cantly increases microbubble appearance, 13 can be performed more accurately. Further investigations demonstrated that the unilateral detection of RLS by power M-mode transcranial Doppler, used in this study, provided an equivalent sensitivity to a bilateral detection, 14 while easier to handle. Recognizing the limitation that, in unusual circumstances, a RLS detected on TCD may be the source of other intracardiac or intrapulmonary shunts and that a PFO may remain silent if it causes left-to-right shunting only, the presence of RLS demonstrated by TCD will, for the remainder of this discussion and manuscript, be assumed to be the consequence of PFO with RLS.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Furthermore, TCD is considerably less invasive for the patient, and the Valsalva maneuver, which signifi cantly increases microbubble appearance, 13 can be performed more accurately. Further investigations demonstrated that the unilateral detection of RLS by power M-mode transcranial Doppler, used in this study, provided an equivalent sensitivity to a bilateral detection, 14 while easier to handle. Recognizing the limitation that, in unusual circumstances, a RLS detected on TCD may be the source of other intracardiac or intrapulmonary shunts and that a PFO may remain silent if it causes left-to-right shunting only, the presence of RLS demonstrated by TCD will, for the remainder of this discussion and manuscript, be assumed to be the consequence of PFO with RLS.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Finally, we recorded microbubble shunting from only a single MCA in our TCD studies. Although this is common practice, there is no consensus as to whether a negative TCD recording from a single artery is sufficient to regard a study as “negative.” The approach published by Jesurum and colleagues, who performed simultaneous recording from both MCAs, may be preferable and is the procedure of choice in the “PREMIUM” trial . Had we employed this methodology, the yield of TCD may well have been greater.…”
Section: Discussionmentioning
confidence: 99%
“…The approach published by Jesurum and colleagues, who performed simultaneous recording from both MCAs, may be preferable and is the procedure of choice in the "PREMIUM" trial. 29,30 Had we employed this methodology, the yield of TCD may well have been greater. However, the fundamental conclusions of our work would not have changed.…”
Section: Timing and Proper Performance Of Valsalva Maneuver: Valsalvamentioning
confidence: 99%